Homogeneidad y diversidad en el patrimonio urbano: casos de El Carmen, San Pedro de Lloc y Huancayo - Córdova Aguilar, Hildegardo (2005)
Patrimony is a heritage that a person or group of persons receives from their ancestors. Urban centres, as well as places, have a set of attributes, which increase with time and little by little they beco me representatives of the historie sequences of their develop ment, giving way to patrimonies.Cities undergo value mutations of their built spaces. In fact, when greater is thecity, greater is the lost of its own spatial references and the absence of identity roots, adds to the disappearance of its communal way of life, re-enforcing any type of unordered behaviors. Fortunately, the globalization process is not lineal and does not lead to automatic homogenization as may be thought. Against this direci:ion there are the revitalization processes of ethnic identities, the construction of their geographic spaces with  new identities  in the distinct zones of cities, and the rebuilding of nationalism.In this study we analyze the cases of El Carmen, a small town of 1.000 people, mainly blacks, located Southeast of the city of Chincha; San Pedro de Lloc, a small city of 9.500 people in the Jequetepeque Valley; and Huancayo, a middle-size city of 400.000 people located in the inter Andean Valley of Mantaro. These centers havedifferent cultural histories from their origins, but with time, little by little they became integrated to the national system.The differences found have cultural-ethnic explanations but also places play a very important role because they give the sense oflocation and belongings to unique landscapes that are kept in the people's memory for undetermined time. Human adaptations toa place are manifested in dances, music, feasts, and in the arrangements of parks, plazas, and avenues, with proper symbols that show to the foreigners an identity that presses to be respected.